Evaluation of Headache-Related Quality of Life and Dry Eyes Following Dermatochalasis Surgery: A Prospective Clinical Study - Ahmadikhatir S; Finskas O; Svedberg K (Clinical Ophthalmology)
Shoyar Ahmadikhatir,1 Oscar Finskas,1 Karin Svedberg1,2 1Region Västra Götaland, Sahlgrenska University Hospital, Department of Ophthalmology, Mölndal, Sweden; 2Department of Clinical Neuroscience, Institute of Neuroscience and Physiology, Sahlgrenska Academy, University of Gothenburg, Gothenburg, SwedenCorrespondence: Shoyar Ahmadikhatir, Department of Ophthalmology, Sahlgrenska University Hospital, Göteborgsvägen 31, Mölndal, SE-431 80, Sweden, Tel +46313421000, Fax +463131412904, Email shoyar.ahmadikhatir@vgregion.sePurpose: To evaluate patients’ headache-related quality of life and dry eyes before and after dermatochalasis surgery of the upper eyelid.Methods: This prospective clinical trial included 29 patients (58 eyes) who underwent dermatochalasis surgery of the upper eyelid at Sahlgrenska University Hospital. The inclusion criteria were bilateral dermatochalasis of the upper eyelid and preoperative headache. Patients were interviewed using the Headache Impact Test (HIT-6) (Version 1.1) and Dry Eye Questionnaire (DEQ-5) to assess headache impact and dry eyes. Pre- and postoperative examinations also included visual acuity, visual field, Schirmer’s test, Break-Up Time (BUT), fluorescein staining, and margin reflex distance (MRD) measurements.Results: Twenty-eight patients (56 eyes) completed the study protocol. The study showed that MRD improved significantly (p < 0.001). Visual acuity (logMAR) improved significantly in both the right eye (p = 0.003) and the left eye (p = 0.017). HIT-6 and DEQ-5 scores also showed significant improvements (p < 0.001). No statistically significant differences were observed in the visual field index (VFI) or pattern standard deviation (PSD). The upper visual field improved significantly in the right eye (p = 0.02) but not in the left (p = 0.39). The Schirmer test showed significant improvement in the left eye (p = 0.04). However, no statistically significant changes were observed in BUT or fluorescein staining.Conclusion: Dermatochalasis surgery of the upper eyelid improved headache-related quality of life; however, the effect on dryness of eyes was more complex. DEQ-5 improved, but that result could not be confirmed in more objective examinations. No deterioration of dryness of the eyes could be found despite a larger palpebral fissure. The surgery provides both functional and cosmetic benefits.Keywords: dermatochalasis, headache, quality of life, dryness of eyes